Accumulation of cellobiose lipids under nitrogen‐limiting conditions by two ustilaginomycetous yeasts, Pseudozyma aphidis and Pseudozyma hubeiensis. Issue 1 (11th October 2012) - Morita, Tomotake; Fukuoka, Tokuma; Imura, Tomohiro; Kitamoto, Dai
Abstract Some basidiomycetous yeast strains extracellularly produce cellobiose lipids (CLs), glycolipid biosurfactants which have strong fungicidal activity. The representative CL producer Ustilago maydis produces CLs together with the other glycolipids, mannosylerythritol lipids (MELs); the preference of the two glycolipids is affected considerably by the nitrogen source. To develop new CL producers, 12 MEL producers were cultured under the nitrogen‐limited conditions. Pseudozyma aphidis and Pseudozyma. hubeiensis were characterized as new CL producers. CL production was induced on three strains, P. aphidis, Pseudozyma graminicola, and P. hubeiensis under these conditions. The putative homologous genes of U. maydis cyp1, which encodes a P450 monooxygenase, essential for CL biosynthesis, were partially amplified from their genomic DNA. The nucleotide sequences of the gene fragments from P. hubeiensis and P. aphidis shared identities with U. maydis cyp1 of 99% and 78%, respectively. Furthermore, all of the deduced translation products are tightly clustered in the phylogenic tree of the monooxygenase. These results suggest that the genes involved with CL biosynthesis must be widely distributed in the basidiomycetous fungi as well as the MEL biosynthesis genes, and thus, the genus Pseudozyma has great potential as a biosurfactant producer.